![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1: Tìm X
a, 32.(x+4)-52=5.22
⇒ 32 .(x+4)-25 =20
⇒9 . (x+4) = 20+25=45
⇒ x+4 = 45: 9 = 5
⇒ x = 5-4 = 1
Vậy x = 1
b,5x+x=39-311:39
⇒ 6x = 39 - 32 =39-9=30
⇒ x = 30 : 6 = 5
Vậy x = 5
c(3x -24 ).73 =2.74
⇒ 3x -24 = 2 . 74 : 73
⇒ 3x - 16 = 2 . 7 = 14
⇒ 3x = 14+16=30
Mà 33=27 , 34 = 81
⇒ x = ∅
Bài 2
a, 66.25+5.66+66.14+33.66
= 66 . ( 25+5+14+33 )
= 66 . 77 = 5082
![](https://rs.olm.vn/images/avt/0.png?1311)
a. 8x+2x =25. 2 mũ 2
8x+2x=100
(8+2)x=100
10x=100
x=100:10
x=10
b.5x+2x=35
(5+2)x=35
7x=35
x=35:7
x=5
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 8x + 2x = 25 . 22
8x + 2x = 100
( 8 + 2 )x = 100
10x = 100
x = 100 : 10
x = 10
b) 5x + 2x = 35
( 5 + 2 )x = 35
7x = 35
x = 35 : 7
x = 5
c) 5x + x = 150 : 2 + 3
5x + x = 75 + 3
5x + x = 78
( 5 + 1 )x = 78
6x = 78
x = 78 : 6
x = 13
d) 6x + x = 511 : 59 + 31
6x + x = 52 + 31
6x + x = 25 + 3
6x + x = 28
( 6 + 1 )x = 28
7x = 28
x = 28 : 7
x = 4
e) 5x + 3x = 36 : 33 . 4 + 12
5x + 3x = 33 . 4 + 12
5x + 3x = 27 . 4 + 12
5x + 3x = 108 + 12
5x + 3x = 120
( 5 + 3 )x = 120
8x = 120
x = 120 : 8
x = 15
![](https://rs.olm.vn/images/avt/0.png?1311)
\(5x+2x=6^2-5^0\Leftrightarrow5x+2x=6^2-1\)
\(\Leftrightarrow5x-2x=36-1\Leftrightarrow5x-2x=35\Leftrightarrow x\left(5+2\right)=35\)
\(\Leftrightarrow7x=35\Leftrightarrow x=35:7\Leftrightarrow x=5\)
\(5x+x=150:2+3\Leftrightarrow5x+x=75+3\)
\(\Leftrightarrow5x+x=78\Leftrightarrow x\left(5+1\right)=78\Leftrightarrow x6=78\)
\(\Leftrightarrow x=78:6\Leftrightarrow x=13\)
a) 5x + 2x = 62 - 50
7x = 35 => x = 5
b) 5x + x = 150 : 2 + 3
6x = 78 => x = 13
c) 6x + x = 511 : 59 + 31
7x = 28 => x = 4
d) 5x + 3x = 36 : 33 x 4 + 12
8x = 120 => x = 15
e) 4x + 2x = 68 - 219 : 216
6x = 60 => x = 10
f) 5x + x = 39 - 311 : 39
6x = 30 => x = 5
g) 7x - x = 521 : 519 + 3 x 22 - 70
6x = 36 => x = 6
h) 7x - 2x = 617 : 615 + 44 : 11
5x = 40 => x = 8
![](https://rs.olm.vn/images/avt/0.png?1311)
B1:
a, 4(a - 3) - (a2 + 2a) - 5a
= 4a - 12 - a2 - 2a - 5a
= - a2 - 3a - 12
b, a(a+3) - [a(a-3) + 2(a+1)]
= a2 + 3a - [a2 - 3a + 2a + 2]
= a2 + 3a - a2 + 3a - 2a - 2
= 4a - 2
B2:
a, 3(x-4) - (2x+3) = 7-2x
=> 3x - 12 - 2x - 3 = 7 - 2x
=> x - 15 = 7 - 2x
=> 3x = 22
=> x = \(\frac{22}{3}\)
b, x(x2-3) - (x3+x) - 5x = (-8)2
=> x3 - 3x - x3 - x - 5x = 64
=> -9x = 64
=> x = \(\frac{-64}{9}\)
c, x(x-1) - 3(x+2) - x2 = -2.33
=> x2 - x - 3x - 6 - x2 = -54
=> -4x = -48
=> x = 12
![](https://rs.olm.vn/images/avt/0.png?1311)
a. x50 = x
\(\Rightarrow\)\(\left[\begin{array}{nghiempt}x=1\\x=-1\end{array}\right.\)
b. 125 = x3
Vì 53 =125 \(\Rightarrow\)x = 5
c.64 = x2
Vì 64 = 82 \(\Rightarrow\) x = 8
d.90 = 10 . 3x
3x= 90 : 10
3x = 9
Vì 32 = 9 \(\Rightarrow\)x = 2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 100 - 7.(x-5) = 68
7.(x - 5) = 100 - 68 = 32
x - 5 = \(\frac{32}{7}\)
x = \(\frac{32}{7}+5=\frac{67}{7}\)
b) 2(x-6)+2227:17=151
2( x -6) + 131 = 151
2 (x - 6) = 20
x - 6 = 20 : 2 = 10
x = 10 + 6 = 16
![](https://rs.olm.vn/images/avt/0.png?1311)
\(5x+2x=6^2-5^0\)
\(7x=36-1\)
\(7x=35\)
\(x=5\)
vậy \(x=5\)
\(5x+x=150:2+3\)
\(6x=75+3\)
\(x=78:6\)
\(x=13\)
vậy \(x=13\)
những câu sau tương tự
1) 5x + 2x = 6^2 - 5^0
=> 7x = 36 - 1 = 35
=> x = 35 : 5 = 5.
Vậy x = 5
2) 5x + x = 150 : 2 + 3
=> 6x = 75+3 = 78
=> x = 78 : 6 =13.
Vậy x = 13
3) 6x + x = 5^11 : 5^9 - 3^1
=> 7x = 5^2 -3 = 25 - 3 = 22
=> x = 22 : 7 = 22 / 7.
Vậy x = 22/7
4) 5x + 3x = 3^6 : 3^3 .4 + 12
=> 8x = 3^3 .4 + 12= 27.4 + 12 = 108 + 12 =120
=> x = 120 : 8 = 15.
Vậy x = 15
5) 4x + 2x = 68 - 2^19 : 2^16
=> 6x = 68 - 2 ^3 = 68 - 8 =60
=> x = 60 : 6 =10.
Vậy x = 10
6) 5x + x = 39 - 3^11 : 3^9
=> 6x = 39 - 3^2 = 39 - 9 = 30
=> x = 30 : 6 =5.
Vậy x =5
7) 7x - x = 5^21 : 5^19 + 3. 2^2 - 7^0
=> 6x = 5^2 + 3.4 - 1 = 25 + 12 - 1 = 36
=> x = 36 : 6 = 6.
Vậy x = 6
8) 7x - 2x = 6^17 : 6^15 + 44 : 11
=> 5x = 6^2 + 4 = 36 + 4 = 40
=> x = 40 : 5 = 8 .
Vậy x = 8
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (2x-1)5 = 2x-1
=> (2x-1)5 - (2x-1) = 0
(2x-1).[(2x-1)4 -1]=0
=> 2x-1 =0 => 2x = 1=> x = 1/2
(2x-1)4 - 1= 0 => (2x-1)4 = 1 = 14 = (-1)4
=> 2x-1= 1 => 2x = 2 => x = 1
2x -1 = -1 => 2x = 0 => x = 0
KL:...
b) 25x.43 = 169
25x = (42)9:43
25x = 418:43
25x = 415 = (22)15 = 230
=> 5x = 30 => x = 6
c) 3x+1+4.3x = 7.36
3x.3+4.3x = 5013
3x.(3+4) = 5013
3x.7 = 5013
3x = 729 = 36
=> x = 6
a, 4.(x-3)=72-13
=> 4(x - 3) = 49 - 1
=> 4(x - 3) = 48
=> x - 3 = 12
=> x = 15
b, 5x+x=150:2+3
=> 6x + = 75 + 3
=> 6x = 78
=> x = 13
a) 4(x-3)=72-13
<=> 4(x-3)=49-1
<=> 4(x-3)=48
<=> x-3=12
<=> x=15
Vậy x=15
b) 5x+x=150:2+3
<=> 6x=75+3
<=> 6x=78
<=> x=13
Vậy x=13